Особливості організації міжкультурної взаємодії учнів у процесі полікультурного виховання - Кендзьор, Петро; Kendzor, Petrо (Східноєвропейський національний університет імені Лесі Українки, 2015)
Умови організації завдань міжкультурної взаємодії учнів у процесі полікультурного виховання – відповідність виховної роботи соціокультурним особливостям виховного середовища; створення умов для набуття особистістю полікультурних здатностей через різноманітні форми діяльності; формування мотивації позитивної соціальної комунікації і дії.Условиями эффективной реализации межкультурного взаимодецйствия учеников в процессе поликультурного воспитания является соответствие воспитательной работы социокультурным особенностям воспитательногй среды; создание условий для овладения поликультурными способностями посредством вовлечения в разнообразные формы деятельности; формирование мотивации позитивной социальой коммуникации и действий.By organizing the educational process in the context of intercultural cooperation, it is necessary to take into account all factors and character of multicultural cooperation in class and other educational environments around students. Common education, work, social-profitable activities, communication promote the formation in pupil the respect to the representatives of other ethnos, religions, cultural and social peculiarities. The expedient selection of appropriate methodology of polycultural education should rely on social and cultural specific of certain social group, age and psychological features of students development, norms and traditions of multicultural cooperation in certain community. The methodjlogy of intercultural cooperation introducing into school promotes the active and interactive cooperation of students, providing the critical thinking of individual in the process of analyzing of different socio-cultural phenomena, as own and others cultures, creating the opportunity of the positive individual identification with certain community in any social and cultural context.
Features of the Organization of Intercultural Interaction of Students in the Process of Multicultural Education.
Keywords: особистість, міжкультурна взаємодія, загальноосвітній навчальний заклад, полікультурне виховання.; личность, межкультурное взаимодействие, общеобразовательное учебное заведение, поликультурное воспитание; personality, intercultural cooperation, secondary educational establishment, multicultural up-bringing.